2018
DOI: 10.18844/prosoc.v5i4.3699
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Ipomoea carnea (jacq.) extracts and chlorpyrifos insecticide against the cotton leafworms, Spodoptera littoralis (Boisd.)

Abstract: The cotton leafworm, Spodoptera littoralis (Boisd.), is an insect that causes serious damages to more than 112 plant species belonging to 44 different families. Botanical extracts of Ipomoea carnea were very efficient against fourth instar larvae of Spodoptera littoralis. Based on LC50 and LC90 values, Ipomoea carnea acetone extracts were recorded 24.622 and 164.947 ppm, respectively. While hexane extracts were 232.677 and 15,377.590 ppm, respectively. Also, the treatment of fourth instar larva of S. littorali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…The acetonic extract was more effective than hexane and ethyl alcoholic extracts. These results were in agreement with Hafez (2001) who tested petroleum ether and acetonic extracts of Iberis amara seeds and Antholyza aehtiopica scale leaves against S. littoralis and Nassar et al, (2015) when studied the toxic effects of acetonic, hexane and alcoholic extracts of the aerial parts of Ipomea carnea against the 4 th instar larvae of S. littoralis.…”
Section: Discussionsupporting
confidence: 90%
“…The acetonic extract was more effective than hexane and ethyl alcoholic extracts. These results were in agreement with Hafez (2001) who tested petroleum ether and acetonic extracts of Iberis amara seeds and Antholyza aehtiopica scale leaves against S. littoralis and Nassar et al, (2015) when studied the toxic effects of acetonic, hexane and alcoholic extracts of the aerial parts of Ipomea carnea against the 4 th instar larvae of S. littoralis.…”
Section: Discussionsupporting
confidence: 90%
“…They represented secondary plant metabolites with insecticidal properties [6]. Current plant I. carnea is called Morning glory in English, belongs to family Convolvulaceae it was utilized in many countries as an antiinflammatory activity, antioxidant activity, embro toxic effect, antifungal activity and insecticidal activity [7,8].The dried powder of leaves composed of alkaloid, reducing sugars, glycosides and tannins [9]. The bioactive compounds against mosquito were contributed to high cellulose and volatile solid content of dried stem material as well as dibutyl phthalate as a biologically active molecule currently was isolated from stem [10].Previous studies were revealed that I. carnea extracts were potent larvicidal activity against mosquito [11].…”
Section: Introductionmentioning
confidence: 99%